Mammary Development and Breast Cancer: The Role of Stem Cells - Ercan, C. (2011)
The mammary gland is a highly regenerative organ that can undergo multiple cycles of proliferation, lactation and involution, a process controlled by stem cells. The last decade much progress has been made in the identification of signaling pathways that function in these stem cells to control self-renewal, lineage commitment and epithelial differentiation in the normal mammary gland. The same signaling pathways that control physiological mammary development and homeostasis are also often found deregulated in breast cancer. Here we provide an overview on the functional and molecular identification of mammary stem cells in the context of both normal breast development and breast cancer. We discuss the contribution of some key signaling pathways with an emphasis on Notch receptor signaling, a cell fate determination pathway often deregulated in breast cancer. A further understanding of the biological roles of the Notch pathway in mammary stem cell behavior and carcinogenesis might be relevant for the development of future therapies.